Becoming a Citizen in the Age of Trump: Citizenship as Social Rights for Latines in Texas - Nancy Plankey-Videla; Mary E. Campbell (Social Sciences)
In the anti-immigrant national context of the first Trump administration, what motivated Latine immigrants in Texas to pursue naturalization? Based on 31 Spanish and English semi-structured interviews conducted during 2017–2019, we examine how lawful permanent residents’ (LPRs’) perceptions of contemporary immigration policy and their social rights affect their motivations to naturalize. Surprisingly, we find that although fear of deportation was an extremely common motivation, it was rarely the residents’ primary motivation. When asked why they wanted to naturalize, our respondents expressed four primary motivations grounded in their claims for social rights: proactive (gain the right to vote, benefit the group), pragmatic (expedite family reunification, access better jobs, benefit the individual), defensive (protect against deportation), and emotional (formalize a sense of belonging). Although 60 percent of interview subjects mentioned some defensive motivations, citing the current national and state political climate as hostile to immigrants, it was the least common primary motivation for naturalization; that is, they named another motivation first as their most important reason for naturalizing. The need to naturalize to protect their social rights in a shifting political context is a strong subtext to subjects’ narratives about why they choose to become citizens. Defensive motivations undergird all other motivations, but the national hostile climate is moderated by relatively positive local interactions with law enforcement and the larger community.